Update about Oralair® as a treatment for grass pollen allergic rhinitis. Issue 5 (30th November 2022) - Klimek, L.; Brehler, R.; Mösges, R.; Demoly, P.; Mullol, J.; Wang, D. Y.; O'Hehir, R. E.; Didier, A.; Kopp, M.; Bos, C.; Karagiannis, E.
ABSTRACT: Sublingual immunotherapy (SLIT) is a well-tolerated, safe, and effective approach to treating allergic rhinitis (AR). Oralair® is a five-grass pollen SLIT tablet containing natural pollen allergens from five of the major grass species responsible for seasonal AR due to grass pollen allergy. Recommended use is in a pre-coseasonal regimen, starting daily treatment approximately 4 months before the start of the pollen season, with treatment then continued daily throughout the season; treatment should continue for 3–5 y. Clinical efficacy and safety of Oralair® in patients with grass pollen-induced AR has been demonstrated in a comprehensive clinical development program of randomized controlled trials. Effectiveness has been substantiated in subsequent observational studies with sustained efficacy following treatment cessation and a favorable level of adherence, quality of life, benefit, and satisfaction for the patients. Supportive evidence for a benefit in reducing the risk or delaying the development of allergic asthma is emerging.